PENGARUH E-LEARNING TERHADAP HASIL BELAJAR SISWA PADA KONSEP SISTEM REPRODUKSI MANUSIA - wadud, abdul (Jurnal Infokes, 2022)
Research has been carried out with the title "The Influence of E-learning on student learning outcomes on the concept of the human reproductive system". This study aims to determine the effect of e-learning on student learning outcomes on the concept of the human reproductive system. The research method used is quasi-experimental and the design used is pretest-posttest control group design. The study was conducted on students of class XI IPA 4 as a control class and XI IPA 5 as an experimental class at MA Negeri 1 Bandung with 31 students in each class. Sampling was done with a purposive sampling technique. To obtain the required data, the instruments used are multiple choice questions as primary data and questionnaires as secondary data. Based on data processing, the average posttest learning outcomes for the experimental class was 63.23 and the control class was 61.74 with the results of hypothesis testing Z count = 0.53 in the Z table acceptance area of 1.96. Based on these results, there is no significant effect of learning through e-learning on student learning outcomes on the concept of the human reproductive system. It can be concluded that e-learning has the same effect as multimedia learning on student learning outcomes. Keywords: E-Learning, Learning Outcomes, Human Reproductive System